Risk factors for tracheostomy requirement in extremely low birth weight infants. (16th February 2018) - Levit, Orly L.; Shabanova, Veronika; Bazzy-Asaad, Alia; Bizzarro, Matthew J.; Bhandari, Vineet
Abstract: Aim: To identify variables that affect the risk of tracheostomy in a population of extremely low birth weight (ELBW) infants. Methods: A retrospective matched case–control study was conducted. ELBW infants with a tracheostomy were compared with controls without tracheostomy. Data collection included demographics, detailed information about each intubation and extubation attempt, the use of steroids and the presence of comorbidities. Statistical analyses include conditional logistic regression and Poisson regression for clustered observations. Results: Twenty-eight ELBW infants with a tracheostomy were identified. Mean gestational age for both cases and controls was 25 weeks (22–29) and 67.9% were males. Tracheostomy was performed on average on day of life 118 (95%CI: 107–128) and weight at tracheostomy was 2877 g (95%CI: 2657–3098). In the final model, cumulative days with an endotracheal tube (ETT) and total number of intubation episodes were associated with a tracheostomy. For each additional day of intubation, odds of tracheostomy increased by 11% (OR = 1.11, 95%CI: 1.01, 1.23) and with each new intubation episode/failed extubation episode, odds of tracheostomy increased by 150% from the previous episode (OR = 2.5, 95%CI: 1.2, 5.2). Conclusions: Greater cumulative exposure to ETT ventilation and number of intubations is associated with having a tracheostomy.